PELATIHAN DAN PENDAMPINGAN MEDIA PEMBELAJARAN BAHASA ISYARAT DI SLB NEGERI 1 PALOPO - Bustamin, Syamsumar; Hamdani, Ibnu Mansyur; Hadi, Abri (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
Education is a universal right, including for children with special characteristics such as deaf students at SLB Negeri 1 Palopo. To support their learning, the use of interactive learning media based on information and communication technology, such as Augmented Reality (AR), is an effective solution. This Community Service aims to implement AR as an interactive and effective sign language learning medium for deaf students. This Community Service involves the introduction of student learning activities in sign language learning and the development of AR-based learning media products. The product is a mobile application that can be accessed using an Android mobile device. The implementation of learning media is carried out through the introduction of application features to teachers and students, as well as direct trials involving parental participation. The use of AR technology in learning media is also considered to provide an interactive and interesting learning experience for students. The implementation of Augmented Reality as an interactive sign language learning media at SLB Negeri 1 Palopo provides positive benefits in the learning of deaf students. This AR learning media can improve students' understanding of sign language in a more interactive and fun way. It also shows the potential of using technology in expanding educational accessibility for students with special needs, such as students who are deaf.